UPAYA MENINGKATKAN PENGETAHUAN, SIKAP DAN KETERAMPILAN PADA IBU BALITA DALAM PEMBERIAN MAKANAN SUMBER VITAMIN A ALAMI DI KOTA YOGYAKARTA - Dewi, Sandra; Ismail, Djauhar Ismail; Paramastri, Ira (STIKES Syedza Saintika Padang, 2023)
Indonesia is still facing four nutrition problems which one of them is Vitamin A deficiency ( KVA )The improvement of nutrition status in the future is facing the changing of community behavior in selecting food sources. Factors fhat influence mothers in giving food are knowledge, attitude, skill, perspective and level of education. One of the objectives of development in the health field in Jogjakarta is to improve the nutrition status of the family. Effort of improving the role of mother can be done through health education in terms of education, attitude and skill with speech and module methods.This research was aimed to find out the influence of speech and module methods in improving knowledge, attitude and skill of mothers of chidren under five years old in giving natral vitamin A food source Analysis of age and education variables in both of the groups was comparable ( p > 0.05 ). Treatment group experienced improvement in knowledge with mean differences from pretest was – 1.0 raised to +0.4 in posttest 1 and + 1.1 in posttest 2 ( p < 0.05 ), and skill with mean differences from pretest 0 raised to + 1.1 in posttest 1 and + 2.5 in posttest 2 ( p < 0.05 )Keywords : Health education, methods of speech and module, knowledge and skill